A Teacher Empowerment Framework for Enhancing Professional Capability: Evidence from a Mixed-Methods Study - Rex U. Celosia; Maria Liesle A. Dopeno; Jay L. Galimpin (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Teacher empowerment remains a critical concern in public education because it influences teachers’ professional agency, participation in school improvement, instructional effectiveness, and capacity to contribute meaningfully to educational change. Building from a previously conducted mixed-method investigation on teacher empowerment among public school teachers and school heads in Tagbilaran City and Bohol Divisions, this article presents the development of a research-based teacher empowerment framework. The empirical foundation of the framework was drawn from quantitative findings involving school administrators and teachers, as well as qualitative insights from selected participants. The original study revealed that school heads perceived teacher empowerment more favorably than teachers themselves, particularly in the domains of decision-making and impact. While professional growth and self-efficacy were rated highly by both groups, teachers reported more moderate levels of empowerment in decision-making. Qualitative findings further identified inclusive leadership, trust, role assignment, support, collaboration, and communication as enabling conditions, while micromanagement, limited autonomy, restrictive decision-making, insufficient engagement, and lack of transparency served as hindering factors. Based on these findings, the proposed framework highlights five key areas: decision-making autonomy, professional development access, trust and recognition, collaborative leadership, and empowerment in practice. The framework offers practical guidance for school heads, teachers, and education supervisors in designing school-level mechanisms that strengthen teacher participation, professional agency, and shared accountability. The article contributes to educational management literature by translating mixed-method findings into an actionable framework for teacher empowerment in public school contexts.